PENGEMBANGAN BAHAN AJAR BERBASIS WEB GOOGLE SITES UNTUK PEMBELAJARAN PERMAINAN BOLA BESAR FUTSAL KELAS IX SMP NEGERI 3 MALANG - Heru Hardiyansyah Cahyana Putra; Rama Kurniawan (Jurnal Pedagogik Olahraga, 2024)
This study aims to develop web-based teaching materials using the Google Sites platform for Physical Education, Sports, and Health (PJOK) subjects on the material of big ball games (futsal) at SMP Negeri 3 Malang. The development of this product uses the ADDIE model, which includes five stages, namely analysis, design, development, implementation, and evaluation. The validation process involved media experts, material experts, and learning experts, which gave very high validity scores, reaching 98%, 91%, and 92% respectively. In addition, trials conducted on two groups of students, a small group of 12 students and a large group of 30 students, also showed very valid results, with an average score of 92% in both groups. This indicates that the product developed meets the eligibility standards from various aspects, both technically and pedagogically. The results of this study indicate that the web-based learning media product developed has great potential to increase learning effectiveness, support the independent curriculum, and be adaptive to the needs and characteristics of students who are increasingly accustomed to digital technology. Thus, this product is worthy to be implemented in PJOK learning at SMP Negeri 3 Malang, and contributes to the development of innovative technology-based learning media.